Studi Kualitatif Permasalahan Ketersediaan Tenaga Kesehatan Pada Puskesmas Di Provinsi Maluku - Rauf, Saidah; Patinassarany, Lisbeth; Sahertian, Betty Anthoineta; Rasako, Hairudin; Latumenase, Rony Alexander; Lestaluhu, Santi Aprilian (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2024)
The Indonesian Ministry of Health's Medium-Term National Development Plan aims to ensure the availability of nine types of basic health workers in at least 83% of Puskesmas by 2024. However, the achievement in Maluku Province is far from the target (12%). This study aims to examine the experiences of health worker placements in Puskesmas in Maluku Province. A qualitative research design was employed, with data collected through in-depth interviews. The factors contributing to the shortage of healthcare personnel in public health centers (Puskesmas) include issues related to information systems healthcare workforce, economic factors, security and facilities, as well as factors of burnout and the imbalance in the production of healthcare personnel. The study concludes that the low availability of health workers in Puskesmas in Maluku is primarily caused by factors such as uneven distribution, lack of interest in serving remote areas, and issues related to data systems and technical competencies. It is recommended that the government enhance data systems and synchronization between health offices and Puskesmas, improve the equitable distribution of health workers, and provide incentives and training to improve the competencies and retention of health workers in remote areas of Maluku Province.